UNVEILING THE LEGAL COMPLEXITIES SURROUNDING DUAL USE OF CHEMICAL IN GLOBAL AND INDONESIAN CONTEXTS - Imtihani, Hajar; Efrila, Efrila; Heridadi, Heridadi (Ridwan Institute, 2024)
The use of white phosphorus as a weapon is highly dangerous, causing direct physical damage to victims and environmental harm. White phosphorus is just one of many dual-use chemicals that have industrial benefits but also pose significant health and environmental risks. This situation leads to violations of fundamental human rights. This study discusses the legal complexities related to the use of dual-use chemicals in both global and Indonesian contexts, with a focus on Indonesia’s Health Law No. 17 of 2023. The research aims to identify legal gaps in the regulation of hazardous chemical use, from both international and national perspectives, and to provide recommendations for improving national regulations to better protect the public from the threats posed by dual-use chemicals. This study uses a normative legal approach with descriptive-analytical methods. It evaluates the gaps between national and international regulations on dual-use chemicals and the practical impact of these differences on public health protection in Indonesia. The study finds significant gaps between national and international regulations, particularly in terms of oversight and regulation of dual-use chemicals. The implementation of current health laws in Indonesia remains weak. International regulations are stricter, but they have not been fully integrated into national policies, resulting in gaps in public health protection from the threats posed by these chemicals.